Joint species distribution models unveil co‐occurrences between freshwater mussels and their fish hosts - Janine P. da Silva; Duarte Vasconcelos Gonçalves; Aina Garcia‐Raventós; Manuel Lopes‐Lima; Simone Varandas; Elsa Froufe; Amílcar Teixeira; Francis K. C. Hui; Ana Filipa Filipe; Ronaldo Sousa (Journal of Biogeography, 2023)
Aim Freshwater mussels are among the most threatened taxa in the world, partially due to the dependence on fish hosts to complete their life cycle. Knowledge about the role of environmental and biotic drivers in determining mussels' distribution is currently lacking. We aimed to assess the role of environmental and biotic drivers in determining the distribution of mussels and their fish hosts and to test if co‐occurrence patterns were able to identify mussel‐host interactions. Location Douro River basin (Iberian Peninsula). Taxon Four freshwater mussels and ten fish hosts. Methods Joint species distribution models (JSDMs) were fitted to presence‐absence records for mussel and fish assemblages. Variance partitioning among environmental variables and latent variables was conducted to determine the environmental versus biotic drivers of species distributions. Resulting matrices of pairwise species co‐occurrences were used to identify co‐occurrence patterns. Results The distribution of host generalist mussel species was mainly explained by environmental variables related to climate and topography. The distribution of the host specialist Margaritifera margaritifera was mainly explained by land use. Strong positive correlations between mussels and the most relevant fish hosts were consistently captured by JSDMs. Co‐occurrence patterns were mainly explained by residual factors, indicating the potential role of biotic interactions. Main Conclusions Biotic interactions were expected to play an important role in explaining mussels' distribution, but the contribution of this factor was only meaningful for the host specialist M. margaritifera . Correlations between mussels and suitable hosts allowed to infer important fish hosts for freshwater mussels in the Douro River basin from distributional data alone. By finding similarities between the ecological requirements of co‐occurring species, conservation measures can be oriented towards several species, which brings a more holistic perspective to the protection of biodiversity.